2022
DOI: 10.1186/s13690-022-00798-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial epidemiology of skin cancer in Iran: separating sun-exposed and non-sun-exposed parts of the body

Abstract: Background Skin cancer is among the most common cancer types with an increasing global trend of incidence rate. This study explores the spatial distribution of skin cancer, considering body sites exposed and not exposed to sunshine separately. Methods We used 4302 skin cancer cases recorded by Fars Cancer Registry in south-western Iran for over 6 years (2011–2017). The variables included in the study were patients’ residence address, gender, age, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 36 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Overall, the trend analysis during the 14-year period shows a relative increase in the incidence of NMSC. Most studies conducted in different parts of Iran have also shown the increasing trend of NMSC in recent years 7,11,13,23,31 and the higher overall incidence rate in men. 7,32 Despite the increasing trend of NMSC in most parts of Iran, a study based on the cancer registration statistics of Iran reported a decreasing trend for skin cancer during 2000-2016, making skin cancer the second most common cancer in Iran.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the trend analysis during the 14-year period shows a relative increase in the incidence of NMSC. Most studies conducted in different parts of Iran have also shown the increasing trend of NMSC in recent years 7,11,13,23,31 and the higher overall incidence rate in men. 7,32 Despite the increasing trend of NMSC in most parts of Iran, a study based on the cancer registration statistics of Iran reported a decreasing trend for skin cancer during 2000-2016, making skin cancer the second most common cancer in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, both forms of skin cancer were more common in men (60.1%), and the men: women ratio was 1.56, which is in line with the reports of the IARC 26 and previous studies. 6,7,9,13,21,23,25,27 Apart from the issue of hijab in women which hinders sunlight exposure, the higher incidence of skin cancer in men could be related to the higher rate of outdoor occupations in men and the subsequent exposure to sunlight and other carcinogenic factors. 3,27 In our study, the highest and lowest ASR of skin cancer was observed in people aged ≥ 85 years for non-melanoma and melanoma, 0-4 years for non-melanoma, and 5-14 years for melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, non-melanoma skin cancer was the second common cancer among both men and women. Studies indicated that this type of cancer was more common in men than in women and was more commonly observed in older age groups and increasing incidence rates reported in Iran [ 46 , 47 ]. Skin cancer is primarily caused by exposure to ultraviolet radiation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A higher R 2 value implies a better fit of the model to the data, suggesting that the model captures a larger portion of the variation in the dependent variable based on the independent variables [29]. R 2 can be calculated using equation (11). (11) [ ] [ ]…”
Section: Model Evaluationmentioning
confidence: 99%
“…Additionally, evidence suggests that outdoor activities, increased exposure to UV radiation, and total sunshine hours can also contribute to the incidence of skin cancer [10]. In this regard, various types of skin cancer are significantly linked to environmental conditions and the level of ultraviolet (UV) radiation exposure [11]. The…”
Section: Introductionmentioning
confidence: 99%